Active Vaccination With EMMPRIN-Derived Multiple Antigenic Peptide (161-MAP) Reduces Angiogenesis in a Dextran Sodium Sulfate (DSS)-Induced Colitis Model - Elina Simanovich; Vera Brod; Michal A. Rahat; Michal A. Rahat (Frontiers in Immunology, 2018)
Ulcerative colitis (UC) is an autoimmune disease that affects the colon and shares many clinical and histological features with the dextran sulfate sodium (DSS)-induced colitis model in mice. Angiogenesis is a critical component in many autoimmune diseases, as well as in the DSS-induced colitis model, and is it partially mediated by EMMPRIN, a multifunctional protein that can induce the expression of both the potent pro-angiogenic vascular endothelial growth factor (VEGF) and matrix metalloproteinases (MMPs). We asked whether targeting EMMPRIN by active vaccination, using a novel, specific epitope in the protein, synthesized as a multiple antigenic peptide (MAP), could trigger beneficial effects in the DSS-induced colitic C57BL/6J mice. Mice were vaccinated with four boost injections (50 μg each) of either 161-MAP coding for the EMMPRIN epitope or the scrambled control peptide (Scr-MAP) emulsified in Freund's adjuvant. We show that male mice that were vaccinated with 161-MAP lost less weight, demonstrated improved disease activity indices (DAI), had reduced colitis histological score, and their colons were longer in comparison to mice vaccinated with the Scr-MAP. The 161-MAP vaccination also reduced serum and colon levels of EMMPRIN, colon concentrations of VEGF, MMP-9, and TGFβ, and vessel density assessed by CD31 staining. A similar effect was observed in female mice vaccinated with 161-MAP, including weight loss, colitis histological score, colon length, colon levels of EMMPRIN and colon concentrations of VEGF. However, for female mice, the changes in DAI values, EMMPRIN serum levels, and MMP-9 and TGFβ colon concentrations did not reach significance. We conclude that our strategy of alleviating autoimmunity in this model through targeting angiogenesis by actively vaccinating against EMMPRIN was successful and efficient in reducing angiogenesis.